Genetic Background Influences Acute Response to TBI in Kindling-Susceptible, Kindling-Resistant, and Outbred Rats - Kotloski, Robert J.; Rutecki, Paul A.; Sutula, Thomas P. (Frontiers in Neurology, 2020)
We hypothesized that the acute response to traumatic brain injury (TBI) shares mechanisms with brain plasticity in the kindling model. Utilizing two unique, complementary strains of inbred rats, selected to be either susceptible or resistant to seizure-induced plasticity evoked by kindling of the perforant path, we examined acute electrophysiological alterations and differences in brain-derived neurotrophic factor (BDNF) protein concentrations after a moderate-to-severe brain injury. At baseline, limited strain-dependent differences in acute electrophysiological activity were found, and no differences in BDNF. Following injury, pronounced strain-dependent differences in electrophysiologic activity were noted at 0.5 minutes. However the divergence is transient, with diminished differences at 5 minutes after injury and no differences at 10 and 15 minutes after injury. Strain-specific differences in BDNF protein concentration were noted 4 hours after injury. A simple risk score model generated by machine learning and based solely on post-injury electrophysiologic activity at the 0.5-minute timepoint distinguished perforant path kindling susceptible (PPKS) rats from non-plasticity-susceptible strains. The findings demonstrate that genetic background which affects brain circuit plasticity also affects acute response to TBI. An improved understanding of the effect of genetic background on the cellular, molecular, and circuit plasticity mechanisms activated in response to TBI and their timecourse is key in developing much-needed novel therapeutic approaches.